Silvopastoral Systems Contribute to Water Buffalo Welfare and Normal Behavior Pattern Under Eastern Amazon Conditions - Santos, Núbia de Fátima Alves dos; Silva, Jamile Andréa Rodrigues da; Araújo, Airton Alencar de; Viana, Rinaldo Batista; Garcia, Alexandre Rossetto; Bezerra, Andréia Santana; Nahúm, Benjamim de Souza; Júnior, José de Brito Lourenço (Journal of Agricultural Studies, 2021)
This research aimed to study the behavior of female Murrah buffaloes in a silvopastoral system. The trial was carried out at Embrapa Eastern Amazon, under Afi climate according to the Köppen classification, between August and November 2009, during the less rainy season. Three different periods of the day were considered during activity evaluation: morning period – between 6:00 AM and 9:55 AM; intermediary period – between 10:00 AM and 1:55 PM; and afternoon period – between 2:00 PM and 5:55 PM. The animals were maintained in a silvopastoral system (SPS) (ST; n=10) with shade from Racosperma mangium. The meteorological variables of temperature and relative air humidity were measured, as well as the following animal behavior variables: time grazing, ruminating and idling, time standing and lying, and time in shaded and non-shaded areas. These variables were compared by T test (P<0.05). Air temperatures were higher in the non-shaded area of the SPS. All activities were reduced in the intermediary period, except idling. The grazing and rumination times in the morning were longer in non-shaded areas, while the time idling standing was longer during the intermediary period in shaded areas as a way of avoiding the harmful effects of the intense solar radiation and high air temperatures of the Amazonian humid climate. Hence, SPSs may contribute to animal welfare and increase their productive behavior.